ANALISIS KEMAMPUAN LITERASI SAINS SISWA SMP NEGERI 1 SURABAYA PADA MATERI SISTEM PEREDARAN DARAH BERDASARKAN TINGKATAN LITERASI SAINS BYBEE - Nur Lailatul Mukaromah; Sabtiawan, Wahyu Budi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the scientific literacy skills of eighth-grade students at SMP Negeri 1 Surabaya on the circulatory system material based on Bybee’s levels of scientific literacy and to analyze the influencing factors. This research used a descriptive quantitative approach with a survey method involving 31 students. The instruments used were a scientific literacy test and questionnaire. Data were analyzed using descriptive statistics, Shapiro-Wilk normality test, and Spearman Rank correlation test. The results showed that students’ scientific literacy skills were in the high category with an average score of 82.50. Students demonstrated good achievement at the functional, conceptual, and multidimensional levels. The correlation test results indicated that students’ internal factors, teacher roles, school facilities, and parental support had no significant relationship with students’ scientific literacy scores. Therefore, improving scientific literacy needs to be supported through contextual learning and critical thinking practices.